Induction of Metallothionein Expression After Exposure to Conventional Cigarette Smoke but Not Electronic Cigarette (ECIG)-Generated Aerosol in Caenorhabditis elegans - Cobb, Eric; Hall, Julie; Palazzolo, Dominic L. (Frontiers in Physiology, 2018)
Introduction: With the invention of electronic cigarettes (ECIG), many questions have been raised regarding their safety as an alternative to smoking conventional cigarettes. Conventional cigarette smoke contains a variety of toxicants including heavy metals. However, ECIG-generated aerosol contains only trace amounts of metals, adding to the argument for it being a safer alternative. In response to heavy metal exposure, metallothioneins are induced in cells to help store the metal, detoxify the body, and are also known responders to oxidative stress. In an attempt to add to the evaluation of the safety of ECIGs, metallothionein expression was quantified using the nematode Caenorhabditis elegans as an assessment of stress induced cellular damage caused by exposure. Methods: Adult nematodes were exposed to either ECIG aerosol or conventional cigarette smoke at doses of 15, 30, and 45 puffs, the equivalent of one, two and, three cigarettes, respectively. Movement, survival and stress-induced sleep were assessed for up to 24 h after exposure. Relative expression levels for mtl-1 and mtl-2, C. elegans metallothionein genes, were analyzed after 1, 5, and 24 h post exposure using quantitative RT-PCR. Results: Nematodes exposed to conventional cigarette smoke underwent stress-induced sleep in a dose dependent manner with animals recovering to values within the range of air control after 5 h post exposure. Those exposed to ECIG aerosol did not undergo stress-induced sleep and were indistinguishable from controls. The expression of mtl-1 increased in a dose and time dependent manner in C. elegans exposed to conventional cigarette smoke, with a maximum expression observed at 5 h post exposure of 45 puffs. No induction of mtl-2 was observed in any animals. Additionally, ECIG aerosol did not induce expression of mtl-1 and mtl-2 at levels different than those of untreated. Conclusions: ECIG aerosol failed to induce a stress response in C. elegans. In contrast, conventional cigarette smoke induced the production of mtl-1 in a manner that correlates with the induction of stress-induced sleep suggesting a stress response to damage. The lack of cellular stress response to ECIG aerosol suggests it may be a safer alternative to conventional cigarettes.